PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA (DPPKB) PONOROGO - Siti Wulansari; Edi Santoso; Eka Destriyanto Pristi (Bussman Journal : Indonesian Journal of Business and Management, 2022)
The development of communication and information technology is growing rapidly resulting in increasingly fierce competition in the world of work, so companies must be able to improve performance in their environment, in order to realize the vision and mission that has been set by the company. This study aims to determine the effect of work environment, work discipline and work motivation on employee performance at the Ponorogo Population Control and Family Planning Agency (DPPKB). This research uses quantitative research. Collecting data in this study, namely primary data obtained from distributing questionnaires. The sample in this study was 115 respondents with a sampling technique using total sampling or census where all members of the population were all sampled or as respondents providing information. The testing stages used include instrument testing, coefficient of determination test and hypothesis testing. The analysis used in this study is multiple linear regression analysis. The results of this study indicate that: (1) the work environment has a positive and significant effect on employee performance, as evidenced by the t-count value of 5.075 > 1.981 t table, while the significant value is 0.000 < 0.05. (2) Work discipline has a positive and significant effect on employee performance, as evidenced by the t-count value of 2.198 > 1.981 t table, while the significant value is 0.030 <0.05. (3) Work motivation has a positive and significant effect on employee performance, as evidenced by the t-count value of 2.686 > 1.981, while the significant value is 0.008 < 0.05. (4) Motivation, discipline and work ethic simultaneously have a positive and significant effect on employee performance as evidenced by the calculated F value of 7.541 > F table 2.86 and the significant value obtained is 0.000 <0.05